Evidence of resident coastal population(s) of false killer whales (Pseudorca crassidens) in northern Australian waters - Palmer, Carol; Martien, Karen K.; Raudino, Holly; Robertson, Kelly M.; Withers, Alan; Withers, Emma; Risk, Robert; Cooper, Dylan; D’Cruz, Ellen; Jungine, Edmund; Barrow, Daniel; Cuff, Nick; et al. (Frontiers in Marine Science, 2023)
To help evaluate the distribution, residency, population size and structuring (and hence conservation status) of the poorly known false killer whale Pseudorca crassidens in northern Australian waters, we undertook studies of sightings, movement patterns based on satellite telemetry, and genetics. Sighting data indicates that false killer whales are regular, year-round inhabitants of coastal areas of northern Australia. Satellite-tagged animals spent extended periods of time in shallow coastal waters, with no tagged animals leaving the continental shelf. The lack of spatial overlap in the areas visited by individuals tagged in the Arafura/Timor Seas compared to those tagged in the Gulf of Carpentaria suggests that there may be more than one population in northern Australia coastal waters. All 14 genetic samples collected across 1600 km of coastline possessed the same newly identified mitochondrial control region haplotype, designated haplotype 45. Notably, haplotype 45 is distinct from all previously published false killer whale haplotypes globally and is most similar to the two haplotypes that typify the Endangered Hawaiian Islands resident false killer whale populations. Based on these results and evidence from recent movement records of those tagged, the false killer whale population(s) in northern Australia are apparently demographically independent population(s). Further assessment of the population conservation status is now required.